Risk Factors of Recurrent Upper Respiratory Tract Infection in Children Aged 3-60 Months at Primary Healthcare Centers (Puskemas) in Gresik - Hubah Asyiroh; Retno Asih Setyoningrum; Widati Fatmaningrum; Budi Utomo (Faculty of Medicine Universitas Airlangga, 2021)
Background: Acute respiratory tract infection (ARTI) is one of the causes of morbidity and mortality in children. This infection may happen in either the upper or lower respiratory tracts. It may also happen recurrently in some children according to the risk factors they have. This study aimed to understand the correlation between risk factors and recurrent upper respiratory tract infection in children aged 3-60 months at primary healthcare centers (Puskesmas) in Gresik.Methods: This study used an analytic observational study with cross-sectional design. The amount of sample used was 110 patients with upper respiratory infection from October 2019-April 2020 at Puskesmas Industri and Puskesmas Alun-Alun, Gresik. Data analysis was performed using chi-square test and logistic regression. The data were taken from medical records as well as questionnaires.Results: The result of bivariate analysis showed that asthma (p = 0.000), exposure to cigarette smoke (p = 0.045), healthy home status (p = 0.002), and the occupancy of the house (p = 0.019) had correlations with the occurrence of recurrent upper respiratory infection. Meanwhile, the multivariate analysis presented some variables which had significant correlation with recurrent upper respiratory tract infection such as asthma (p= 0.000), exposure to cigarette smoke (p = 0.012), and healthy home status (p = 0.001).Conclusion: There was a strong relationship between asthma, exposure to cigarette smoke, and healthy home status with the occurrence of recurrent upper respiratory tract infection (URTI) in children.